DEAGREGASI EKSTRAK KASAR PIGMEN (Sargassum crasifolium) J.G. AGARDH DALAM PELARUT ASETON DAN METANOL - EDWIN MAHENDRA; LIA KUSMITA; A.B. SUSANTO; LEENAWATY LIMANTARA (Akuatik: Jurnal Sumberdaya Perairan, 2008)
Several kinds of algae have high economical value because its nutrition and chemical composition can be used in every social aspects. One of them is Brown algae, Sargassum crasifolium which contains photosynthesis pigment, that is chlorophyl a and c. According to Goodwin (1974) and Fitton (2005) this algae is very rich of karotenoid, a kind of fukosantin. According to Gross (1991), chloropyhl will be easy to have degradation if there is extremely environmental changing, for instances: temperature, light intensity, and acid. This research is aimed to know the influence of acid on the aggregate and rough extract spectrum system of Sargassum crasifolium in aseton and metanol by in vitro which has been formed after adding water. Adding acid either asetat acid or hydrochloric acid forms Feofitin Tang indicated by the changing of rough extract spectrum system of Sargassum crasifolium in Qy, Qx and Soret. Kinds of solvent and amount of acid do influence the extract deaggregation process of Sargassum crasifolium. Hydrochloric acid and CH3COOH are able to deaggregate the extract of Sargassum crasifolium in aseton and metanol which has been formed after adding water. If we compare them, HCL will be more significant than CH3COOH to deaggregate.